Marcas de autoria em turma de alfabetização sob a perspectiva da AD francesa - Rodrigues, Susane Andradde (2019)
This dissertation aims to analyze whether the students in the literacy stage, in the 1st year of elementary school, produce singular gestures of interpretation, within their own formulations of meaning through an intervention that took place in the classroom, with didactic material produced under the discursive bias. The theoretical perspective on which this work is based is that of Discourse Analysis from a Pecheutian perspective. The choice for this theoretical path is due to the fact that we perceive the language not in its homogeneity and transparency, but in its effects of meaning and opacity. By providing the student with the possibility of gestures of interpretation through polysemy, ludic pedagogical discourse and controversial pedagogical discourse, it is hoped that the student can assume the position-author when talking about himself, producing his own and possible meanings. The state public school where the research was conducted is located in the municipality of Sant’Ana do Livramento, in Rio Grande do Sul, in a region bordering Uruguay. The class contained twenty students, eleven girls and nine boys. The proposal to apply didactic material with a discursive and also systemic bias arose from an intervention that occurred in this same class at the beginning of the school year. In this previous intervention, students showed affiliation to hegemonic discursive, black students represented themselves and their families with fair skin and blond hair, and women were always engaged in domestic activities. Through working throughout the year and applying a new didactic intervention, it was realized that students can show improvements in aspects related to language skills, in the process of literacy, by having contact with the language and its code and also the consider the language in its opacity. When proposing a work that allows affiliation to other discursive formations, it was observed that singular gestures of interpretation are possible to be produced and at the same time there is a break with the stabilized and, thus, favoring the student to develop authorship.